2016
DOI: 10.3758/s13423-016-1011-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile technology habits: patterns of association among device usage, intertemporal preference, impulse control, and reward sensitivity

Abstract: Mobile electronic devices are playing an increasingly pervasive role in our daily activities. Yet, there has been very little empirical research investigating how mobile technology habits might relate to individual differences in cognition and affect. The research presented in this paper provides evidence that heavier investment in mobile devices is correlated with a relatively weaker tendency to delay gratification (as measured by a delay discounting task) and a greater inclination toward impulsive behavior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 40 publications
15
80
4
1
Order By: Relevance
“…In contrast, those who were unable to inhibit their Internet use may have known that it was distracting but felt compelled to use it anyway. A recent study provides some support for this hypothesis; people who engaged more heavily with mobile devices were less able to delay gratification and had a greater tendency for impulsive behaviors (Wilmer & Chein, 2016). Further work is needed to understand whether students who rated their use as having a disruptive effect are using the Internet because of a compulsion to do so.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those who were unable to inhibit their Internet use may have known that it was distracting but felt compelled to use it anyway. A recent study provides some support for this hypothesis; people who engaged more heavily with mobile devices were less able to delay gratification and had a greater tendency for impulsive behaviors (Wilmer & Chein, 2016). Further work is needed to understand whether students who rated their use as having a disruptive effect are using the Internet because of a compulsion to do so.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in our own lab (Wilmer and Chein, 2016), we used a measure of self-reported mobile technology usage in an attempt to mine the potential relationship with delay of gratification. We observed a significant negative correlation between participants’ mobile technology usage and their “indifference point” and discounting rate in a delay discounting paradigm.…”
Section: Mobile Technology Use Delay Of Gratification and Reward Prmentioning
confidence: 99%
“…This lack of self-control is intrinsically linked to problematic smartphone use. Indeed, a consistent body of research has shown that low levels of self-control not only predict high-frequency usage of smartphones (Wilmer and Chein, 2016;Berger et al, 2018) but also link to smartphone addiction such as withdrawal symptoms, mood changes and cyberspace-oriented relationship (Gökçearslan et al, 2016;Jiang and Zhao, 2016;Yun et al, 2016;Berger et al, 2018).…”
Section: Self-control As a Moderatormentioning
confidence: 99%